Real-Time Water Quality Monitoring with Multi-Sensors - Nizam Husen, Mohd; Ismail, Roslan; Hamzah, Robiah (International Journal of Engineering and Technology, 2018)
Water quality monitoring plays an important role in human well-being, environmental preservation and sustainability. This paper presents the study that has been carried out on the development of water quality monitoring with the tenacity of alerting the user with real-time and online water quality information based on important parameters through a web-based dashboard. The sensors are able to measure the parameters of water quality, such as turbidity, pH, temperature, and the level of the water. Audio and coloured lightings alert are triggered when any water quality parameter reaches unsafe levels. A Wi-Fi transmitter module sends the data to the receiving node over long distance range and display the output in real-time. The result demonstrates that a real-time with multi-parameter remote monitoring of water quality data can be precisely attained and displayed in real-time by using the proposed monitoring system.Â Â